The effect of housing micro-finance on household welfare - Sobukwe-Whyte, Akyere Andiswa (Research of GSB, 2017)
The affordable housing crisis in South Africa has created a need for better quality and efficient housing alternatives. The aim of this research is to identify how housing microfinance contributes towards improved living conditions and welfare of low-income households through a case study analysis. Data was collected from employees and beneficiaries of Ikhayalami's loan finance programme using observations, pictures and semi structured individual interviews. Data was analysed for content with the aim of interpreting emerging trends and concepts. The findings reveal a significant positive effect via an increase in community status and housing conditions. If afforded sufficient infrastructure and support – housing microfinance has the potential to grow in scale and move developmental objectives forward.